Pengaruh Komunikasi Terapeutik Perawat terhadap Tingkat Kecemasan Keluarga Pasien Di Ruang Perawatan Intensif - Rizki Muliani; Andria Pragholapati; Irman (Poltekkes Kemenkes Kendari, 2020)
Family anxiety arises due to the threat of death, disability, and expensive treatment costs. Efforts to reduce the level of anxiety are with psychotherapy through therapeutic communication interactions by nurses. This study aims to determine the effect of therapeutic communication on anxiety levels.The research method used was a pre-experiment using one group pretest and posttest design. A total of 30 respondents were recruited by consecutive sampling in this study. Data obtained using the ZSAS (Zung-Self Anxiety Scale) instrument. Data analysis uses a t-test: two-sample assuming unequal variances.The results showed that the average anxiety level before and after therapeutic communication was 42.73 and 36.43. Anxiety level before therapeutic communication is mild (56.7%) and moderate (43.3%), and the anxiety level thereafter is mild (100%). The T-test value obtained Account 4.49 with a P-value of 0,000 and a correlation of 0.613. Thus it can be concluded that there is a significant influence between the provisions of therapeutic communication with the level of family anxiety of patients treated in the Intensive Space.